+0  
 
0
31
2
avatar+247 

Find the constant term in the expansion of $$\left(10x^3-\frac{1}{2x^2}\right)^{5}$$

Darkside  Sep 11, 2018
 #1
avatar
0

expand  (10 x^3 - 1/(2 x^2))^5=100,000 x^15 - 25,000 x^10 - 1/(32 x^10) + 2,500 x^5 + 25/(8 x^5) - 125 - the constant term.

Guest Sep 11, 2018
 #2
avatar+20009 
+1

Find the constant term in the expansion of $$\left(10x^3-\frac{1}{2x^2}\right)^{5}$$

 

\(\begin{array}{|rcll|} \hline && \left(10x^3-\dfrac{1}{2x^2}\right)^{5} \\\\ &=& \left(\dfrac{10x^3\cdot 2x^2-1}{2x^2}\right)^{5} \\\\ &=& \left(\dfrac{20x^5-1}{2x^2}\right)^{5} \\\\ &=&\dfrac{1}{\left(2x^2 \right)^5} \left( 20x^5-1 \right)^{5} \\\\ &=&\dfrac{1}{ 2^5x^{10} } \left( 20x^5-1 \right)^{5} \\\\ &=&\dfrac{1}{ 32x^{10} } \left( 20x^5-1 \right)^{5} \\\\ &=&\dfrac{1}{ 32x^{10} } \left[ \dbinom{5}{0}\left(20x^5 \right)^5 -\dbinom{5}{1}\left(20x^5 \right)^4 +\dbinom{5}{2}\left(20x^5 \right)^3 \\ -\dbinom{5}{3}\left(20x^5 \right)^2 +\dbinom{5}{4}\left(20x^5 \right) +\dbinom{5}{5}(-1)^5 \right] \\\\ &=&\dfrac{1}{ 32x^{10} } \left[ \dbinom{5}{0} 20^5x^{25} -\dbinom{5}{1} 20^4x^{20} +\dbinom{5}{2} 20^3x^{15} \\ { \color{red}-\dbinom{5}{3} 20^2x^{10} } +\dbinom{5}{4} 20x^5 -\dbinom{5}{5} \right] \\ \hline \end{array}\)

 

Constant term:

\(\begin{array}{|rcll|} \hline && \dfrac{1}{ 32x^{10} }\left[ { \color{red}-\dbinom{5}{3} 20^2x^{10} } \right] \\\\ &=& -\dfrac{1}{ 32x^{10} } \dbinom{5}{3} 20^2x^{10} \\\\ &=& -\dfrac{20^2}{ 32 } \dbinom{5}{3} \quad & | \quad \dbinom{5}{3} = \dbinom{5}{5-3}=\dbinom{5}{2}=\dfrac{5}{2}\cdot \dfrac{4}{1} = 10 \\\\ &=& -\dfrac{20^2\cdot 10}{ 32 } \\\\ &=& -\dfrac{4000}{ 32 } \\\\ &\mathbf{=}& \mathbf{-125} \\ \hline \end{array}\)

 

laugh

heureka  Sep 12, 2018

4 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.